A Need Analysis for Developing Arabic Writing Materials: A Study at Higher Education Institution - Rustamaji, Rustamaji; Anhar, Anhar; Nurlaila, Riza; Rifki, Muh (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This study aimed to explore the needs for developing materials to improve Arabic writing skills at University of Darussalam Gontor (UNIDA Gontor). The study utilized the preliminary stage of a research and development research design, aiming to address current deficiencies in instructional materials. The primary objective was to analyse the requirements of both students and lecturers. The data were collected using a combination of observation, documentation analysis, and questionnaires. The documentation analysis showed UNIDA Gontor's dedication to multilingual competency, ensuring focused and comprehensive Arabic writing instruction. The results of survey questionnaire revealed the existence of variations in instructional material, which caused disparity in how materials were understood. The data also demonstrated that there was a need for alignment of teaching materials with UNIDA's language standards. This research summarized the needs of both lecturers and students for developing Arabic teaching materials that met the requirements of the university and enhanced students’ proficiency in Arabic writing.